The contribution of food composition resources to nutrition science methodology. Issue 3 (September 2017) - Finglas, P.; Roe, M.; Pinchen, H.; Astley, S.
Abstract: Advances in nutrition science methods and tools have underpinned better understanding of the complex interactions between diet, nutrition and health. One example is the development of food composition tables, which provide detailed information about the energy and nutrient content of foods. They are important in many fields, including clinical practice and research, and are used in a variety of ways; for example, to assess national population‐level programmes and surveys, formulate emergency food supplies and develop therapeutic diets. In recent years, food composition tables have widened in scope and accessibility but most do not include bioactive compounds, the consumption of which is associated with reduced risk of cancer and cardiovascular disease. Established in 2009, European Food Information Resource ( EuroFIR ) Association Internationale Sans But Lucratif ( AISBL ) is a non‐profit member‐based association in Belgium and a leading advocate for food information in Europe. It promotes the use of food composition data across the wider food, nutrition and health research and policy landscapes, raises awareness and understanding of the value of these data, especially for consumers in making healthier dietary choices, and works with other organisations [ e.g . Food and Agriculture Organization (FAO) of the United Nations] to facilitate improved data quality, storage and access to encourage wider exploitation of food composition data for both research and commercial purposes. EuroFIR has produced a range of tools to help data compilers and helped develop a European standard for food composition data to support the exchange and comparison of data. It is essential that investment to improve these tools and develop new methods continues, especially in regions without food composition databases. Such activities also need to be cost‐effective and scientifically robust, and engage effectively with stakeholders.